Successful Management of a Huge Pulmonary Hydatid Cyst with Lung-Preserving Surgery - Armin Amirian; Bizhan Ziaian; Amirhossein Erfani; Reza Shahriarirad; Keivan Ranjbar (Case Reports in Surgery)
The lung is the second most commonly involved organ in humans by hydatid disease. Management of large pulmonary hydatid cysts is a great challenge for thoracic surgeons. Lung resections should be considered the last choice for huge pulmonary hydatid cysts when the lung expansion is not optimal after cyst removal. Here, we present a case of huge lung hydatid cyst involving the entire right lower lobe which was successfully managed by lung-preserving surgery in which the postoperative course showed gradual resolution of the involved lobe during a one-year follow-up.